Study of radiative magneto-non-Newtonian fluid flow over a nonlinearly elongating sheet with Soret and Dufour effects. (16th February 2023) - Biswal, Manasa Manjari; Swain, Kharabela; Dash, Gouranga Charan; Ojha, Kanakalata
Abstract: Casson fluid model is extensively used for modeling of blood flow in thin arteries at low shear rates. The current article investigates the Soret and Dufour effects on free convective flow of Casson fluid over a nonlinearly elongating sheet embedded in a porous medium. Free convection: Flows arising solely due to the difference in density caused by temperature differences. The exponential space-based heat source/sink and thermal radiation are also incorporated in the heat transfer equation. Similarity solution was obtained by using suitable transformations and the transformed equations are solved by using the Runge–Kutta fourth-order method with a shooting technique by the help of the MATLAB code. The impacts of operating parameters on velocity, temperature, and concentration distributions are explained through graphs and tables. Important findings of the analysis are: Dufour and Soret effects serve as the surface coolant and maintenance of solutal deposition-free surface. Applied magnetic field and heavier diffusing species with suction lead to thinner boundary condition preventing vorticity diffusion.